Recent Advances Of Pollutants Degradation In Different Environment By Zro2 Based Catalyst Activated Peroxymonosulfate - Hamza Khaliq; Faiza Shahzad; Arslan Riaz; Muhammad Mohsin; Rana Mohsin Ali (Citakonsultindo, 2025)
Peroxymonosulfate (PMS) based advanced oxidation processes (AOPs) have drawn great attention as potential technology for abatement of the refractory organic pollutants in water and soil. Zirconium dioxide (ZrO2) has garnered substantial research interest in the field of photocatalytic water treatment due to its appealing properties, such as thermal stability, considerable physical strength, and strong chemical resistance. Fe, Mn and a bimetallic Fe, Mn catalysts supported on ZrO2 were synthesized and tested for the activation of persulfate (PS) and peroxymonosulfate (PMS) in the degradation reaction of three different organic compounds: cinnamic acid (CA), benzoic acid (BA), and catechol (C). The reversible conversion between ZrS3 and ZrS2 has been observed for the first time by thermal decomposition of ZrS3 at 650 °C and sulfurization of ZrS2 in sulfur vapor at 550 °C. This result suggests a potential application of ZrS2 in the H2S splitting process for H2 recovery. Carbothermal reduction of Zr-sucrose gels powders into nano-phase ZrC, or ZrC-Zr (C,O) core-shell powders, via a composite of 2–4 nm sized ZrO2 and amorphous carbon, is described. In future, various techniques have been utilized to enhance the efficiency of zirconium dioxide such as doping, metal loading. Although co-catalysts have gained a lot of interest by researchers, more efforts should be directed in strengthening the binding force between the co-catalyst and the semiconductor. Moreover, high cost of noble metals, aggregation and corrosion can be overcome by replacing the noble metals with cheap transition metals; thus more investigation is required in that field.